To solve the equation \( 10.25(x - 4.4) = 69.7 \), follow these steps:
-
Distribute \( 10.25 \) on the left side:
\[ 10.25x - 10.25 \cdot 4.4 = 69.7 \]
Calculate \( 10.25 \cdot 4.4 \):
\[ 10.25 \cdot 4.4 = 45.1 \]
So the equation now becomes:
\[ 10.25x - 45.1 = 69.7 \]
-
Isolate the term with \( x \) by adding \( 45.1 \) to both sides:
\[ 10.25x = 69.7 + 45.1 \]
Calculate the right side:
\[ 69.7 + 45.1 = 114.8 \]
Now we have:
\[ 10.25x = 114.8 \]
-
Solve for \( x \) by dividing both sides by \( 10.25 \):
\[ x = \frac{114.8}{10.25} \]
Calculate the division:
\[ x \approx 11.2 \]
Thus, the solution for \( x \) is:
\[ \boxed{11.2} \]